Isolating a Mental Health Effect of a Change in Housing Affordability - Subramanian, S.V.; Baker, E; Mason, K; Kavanagh, A; Bentley, R (My University, 2011)
Evidence about the mental health consequences of unaffordable housing is limited. Using data from seven waves of the Household, Income and Labour Dynamics in Australia (HILDA) survey we investigated whether people whose housing became unaffordable experienced a corresponding deterioration in their mental health (measured using SF-36 MCS), over and above other forms of financial stress. We hypothesised that measurable mental health effects of poor housing affordability would be limited to lower income households as high housing costs will reduce their capacity to purchase other essential non-housing needs (e.g. food). Importantly, we sought to isolate the effect of unaffordable housing from the effects of living in a low income household. We used fixed-effects longitudinal regression to analyse 38,610 responses of 10,047 individuals aged 25 to 64 years who participated in the HILDA survey between 2001 and 2007. We compared within-person changes in mental health in two groups of respondents: those who remained in affordable housing over two consecutive waves (reference group) and those who had moved from affordable to unaffordable housing over two waves (comparison group). For individuals living in low income households, entering unaffordable housing was independently associated with a small corresponding decrease in their mental health score independent of changes in equivalised household income, or having moved house (Beta=-1.19, 95% CI: -1.97, -0.41). As anticipated, we found no evidence of a similar association in higher income households. We conclude that entering unaffordable housing is detrimental to the mental health of individuals residing in low income households.
Keywords: Housing -- Affordability; Health -- Mental; Health; Housing; Health and wellbeing; Housing, communities and neighbourhoods; Health; Housing, communities and neighbourhoods